Modern Training Approaches for Enhancing Motor, Technical and Psychological Development In Beginner Gymnasts - Adilbekov, Ulugbek (Indonesian Journal Publisher, 2025)
Artistic gymnastics is a complex coordination sport demanding exceptional strength, mobility, balance, neuromuscular control, spatial awareness, and precise technical execution. The initial stage of preparation plays a decisive role in shaping motor habits, psychological readiness, injury resistance, and long-term performance potential. This study analyzes modern training technologies and pedagogical strategies designed to improve the development of beginner gymnasts. Drawing from international literature, Russian scientific schools, and Central Asian methodological traditions, the paper identifies the most effective approaches to training novice gymnasts using technology-assisted feedback, modular skill progressions, flexibility enhancement systems, vestibular training, biomechanical modeling, and athlete-centered pedagogy. Results show that early exposure to motor coordination exercises integrated with biomechanical cues accelerates the acquisition of essential skills such as handstands, cartwheels, basic acrobatics, balances, and transitions. Visual feedback using slow-motion analysis and movement diagrams improves technical accuracy and promotes self-regulated learning. Vestibular stimulation through trampolines, balance beams, and rotational platforms enhances spatial awareness and air sense. Psychological readiness is improved through gamification, progressive exposure to fear-inducing elements, and emotionally supportive coaching styles. Flexibility development using hybrid stretching methods significantly strengthens performance potential while reducing injury risk. Overall, the study concludes that combining traditional gymnastics pedagogy with modern technology-supported training creates a high-efficiency developmental framework. This integrated model fosters long-term athlete retention, reduces technical errors, and accelerates gymnastic skill acquisition. Therefore, scientific, individualized, and psychologically supportive training systems are essential for preparing beginner gymnasts to progress safely and successfully toward advanced stages of gymnastics performance.